2015
DOI: 10.1007/s12010-015-1692-1
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Various Aromatic Compounds by Enriched Bacterial Cultures: Part B—Nitrogen-, Sulfur-, and Oxygen-Containing Heterocyclic Aromatic Compounds

Abstract: Present study focused on the biodegradation of various heterocyclic nitrogen, sulfur, and oxygen (NSO) compounds using naphthalene-enriched culture. Target compounds in the study were pyridine, quinoline, benzothiophene, and benzofuran. Screening studies were carried out using different microbial consortia enriched with specific polycyclic aromatic hydrocarbon (PAH) and NSO compounds. Among different microbial consortia, naphthalene-enriched culture was the most efficient consortium based on high substrate deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…It has been reported in the literature that benzofuran can be cleaved at the oxygen bond in its heterocycle [18,19]. Oberoi et al described the aerobic bacterial decomposition of benzofuran to carbon dioxide and water, with either catechol or salicylic acid as possible intermediates [18]. These products have also been observed after metabolism in flavonol compounds [20].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in the literature that benzofuran can be cleaved at the oxygen bond in its heterocycle [18,19]. Oberoi et al described the aerobic bacterial decomposition of benzofuran to carbon dioxide and water, with either catechol or salicylic acid as possible intermediates [18]. These products have also been observed after metabolism in flavonol compounds [20].…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies that have measured the concentrations of PAH-TPs and PACs pre- and post-remediation (Table S1), bioremediation ,,,,, and chemical oxidation are the two most prominent types of remediation that researchers prefer to use and investigate. Most of the bioremediation studies relied on bioslurry or bioreactor treatment, although studies by Steinhart and co-workers showed the applicability of composting in decreasing PAC concentrations. , Bioremediation studies also covered other compounds beyond PAH 16.…”
Section: Chemical Analysis Of Pah-tps and Pacs Pre- And Post-remediationmentioning
confidence: 99%
“…Most of the bioremediation studies relied on bioslurry or bioreactor treatment, although studies by Steinhart and co-workers showed the applicability of composting in decreasing PAC concentrations. , Bioremediation studies also covered other compounds beyond PAH 16. For example, the formation of alkylated PAHs and PASHs TPs is measured in several of the bioremediation studies, ,, while measurements of PANHs, PAOHs, and PASHs pre-bioremediation , and carboxylic acids and other smaller TPs post-remediation have also been performed. , Lemieux et al measured an increase in PASH concentration post-remediation, though the exact biological mechanism leading to the increase in the concentration of PASHs was not elucidated . The inclusion of a diverse group of compounds provides a fuller picture of the presence and biodegradation of PACs in contaminated soil samples.…”
Section: Chemical Analysis Of Pah-tps and Pacs Pre- And Post-remediationmentioning
confidence: 99%
“…Quinoline also is an ubiquitous environmental pollutant released from coal processing, creosote wood preservation and shale oil production, which may result in the contamination of sediments, soil and groundwater . Due to the toxic and harmful effects of quinoline to organisms, it is essential to develop an efficient way to eliminate this contaminant from the environment, and the biological techniques are considered as eco‐friendly and cost‐effective alternatives to physicochemical methods …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Due to the toxic and harmful effects of quinoline to organisms, it is essential to develop an efficient way to eliminate this contaminant from the environment, and the biological techniques are considered as eco-friendly and cost-effective alternatives to physicochemical methods. 5,6 A number of microorganisms with the capability of quinoline biodegradation under aerobic or anaerobic conditions have been isolated from petroleum-contaminated soils, sewage and activated sludge. 1,2 Pseudomonas is the most reported quinoline degrader, 1,7,8 and others include Rhodococcus, 9,10 Bacillus, 11 Comamonas 12,13 and the filamentous fungus Cunninghamella elegans.…”
Section: Introductionmentioning
confidence: 99%